Cost Analysis for an Actor-Based Workflow Modelling Language - Ali, Muhammad Rizwan; Pun, Violet Ka I (Anais do Simpósio Brasileiro de Métodos Formais (SBMF); 2021: Anais do XXIV Simpósio Brasileiro de Métodos Formais, 2021)
Workflow planning usually requires domain-specific knowledge from the planners, making it a relatively manual process. In addition, workflows are largely cross-organisational. As a result, minor modifications in the workflow of a collaborative partner may be propagated to other concurrently running workflows, which may result in significant adverse impacts. This paper presents a resource-sensitive formal modelling language, RPL. The language has explicit notions for task dependencies, resource allocation and time advancement. The language allows the planners to estimate the effect of changes in collaborative workflows with respect to cost in terms of execution time. This paper proposes a static analysis for computing the worst execution time of a cross-organisational workflow modelled in RPL by defining a compositional function that translates an RPL program to a set cost equations.